Financial Sector and Aggregate Import Demand: A General Equilibrium Perspective with Japan Data - Tuck Cheong Tang (Asian Academy of Management Journal of Accounting and Finance, 2018)
This study explores the role of financial sector on import demand behaviour (the real sector) from general equilibrium perspective, which is based on the portfolio balance approach to capture financial market. Japan’s data support partially this hypothesis given noncointegration finding, while foreign interest rate is significant i.e. reduces Japan’s imports. Growth in foreign income is the most influential factor, and domestic economic growth both make more imports. However, the relative price of domestic goods, and domestic interest rate are insignificant. Japan’s monetary policy (interest rate) is inappropriate in altering the behaviour of imports in Japan, but fiscal policy that influences Japan’s economic growth.